Survival of potentially probiotic enterococci in dairy matrices and in the human gastrointestinal tract - Pimentel, Lígia L. (2013)
The aim of this study was to investigate the stability of Enterococcus strains isolated from a traditional Portuguese cheese and previously proved to be safe, in dairy matrices, and to assess survival of the best strains in the human gastrointestinal (GI) tract. Enterococcus faecium 32 and Enterococcus durans 37 were added to yoghurt that was ingested by 4 healthy adults. Detection of the enterococcal strains was performed with RAPD-PCR. The intervention trial showed transient colonisation with both strains, via presence in faeces during the ingestion period and disappearance by 10 d post-ingestion. Viable numbers of enterococci increased during the consumption period by 1.8e4.4 log-values, and returned to baseline level during the follow-up period. Based on data of the dairy matrix stability trials and human intervention study involving yoghurt ingestion, E. faecium 32 survived well both in the food matrix and in the human GI tract, thus showing probiotic potential.